Effects of dose response load squat jump training on muscle strength, structure and performance - Coratella, G.; Annicchiarico, M.; Trepin, M.; Impellizzeri, F. M.; Schena, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Squat jump training is a common method to improve athletic performance. The load that maximize power is around 30% of maximal dynamic strength, i.e. body weight only.(Cormie 2007) However, also weighted jump training has been proved effective to enhance jump or sprint(Mc Bride 2002) Few studies measured changes in muscle mass and architecture to better understand physiological mechanisms those lead to a better field performance. Aim or the study is to evaluate a dose response effect of weighted or unweighted squat jump training on muscle strength, mass structure, jump and sprint ability. Methods: Forty eight healthy students were randomly assigned to body weight only (BW), 25% body mass weighted squat jump training (WJ) and control group (CON).Isokinetic quadriceps strength(MVC), lower limbs total lean mass (DEXA), architectural adjustments (ultrasound), Squat jump (SJ), 30m dash, 20+20m shuttle and ability T test were assessed before and after 8 weeks of 60 maximal jumps, twice a week. All the dependent variables were analyzed after log transformation with ANCOVA using the baseline values as covariate and factor "group" as independent variable. Results: No differences appeared in CON. Compared to baseline, BW improved MVC (23%,16 to 30,p<0,001), lean mass (2%,1 to 4 p<0,05), fascicle length (11%,7 to 16, p<0,001), SJ (10%,6 to 15, p<0,001), 20+20m(-3%,-5 to -1 p<0,05). Compared to baseline, WJ improved MVC(22%,15 to 29,p<0,001), lean mass(5%,3 to 7, p<0,001) fascicle length (5% 0 to 9,p<0,05), SJ(5%,0 to 10,p<0,05), 20+20m(- 3%,-6 to -1,p<0,01), 30m(-3% -1 to -5,p<0,01). All parameters were significantly different from CON. BW had significant alterations in muscle architecture compared to WJ, while the latter improved 30m dash and T Test running test more than BW. Discussion: Jump training improved task related quadriceps strength, also by an increment of lower limbs lean mass, that caused a power transfer in jumping and shuttle test. Greater velocity contractions in BW caused different architectural alterations(Blazevich 2003). Higher changing direction agility and sprint power could be related to increased strength expression in WJ.